Transcriptional regulatory networks underlying gene expression changes in Huntington's disease. Issue 3 (26th March 2018) - Ament, Seth A; Pearl, Jocelynn R; Cantle, Jeffrey P; Bragg, Robert M; Skene, Peter J; Coffey, Sydney R; Bergey, Dani E; Wheeler, Vanessa C; MacDonald, Marcy E; Baliga, Nitin S; Rosinski, Jim; Hood, Leroy E; et al.
Abstract: Transcriptional changes occur presymptomatically and throughout Huntington's disease (HD), motivating the study of transcriptional regulatory networks (TRNs) in HD. We reconstructed a genome‐scale model for the target genes of 718 transcription factors (TFs) in the mouse striatum by integrating a model of genomic binding sites with transcriptome profiling of striatal tissue from HD mouse models. We identified 48 differentially expressed TF‐target gene modules associated with age‐ and CAG repeat length‐dependent gene expression changes in Htt CAG knock‐in mouse striatum and replicated many of these associations in independent transcriptomic and proteomic datasets. Thirteen of 48 of these predicted TF‐target gene modules were also differentially expressed in striatal tissue from human disease. We experimentally validated a specific model prediction that SMAD3 regulates HD‐related gene expression changes using chromatin immunoprecipitation and deep sequencing (ChIP‐seq) of mouse striatum. We found CAG repeat length‐dependent changes in the genomic occupancy of SMAD3 and confirmed our model's prediction that many SMAD3 target genes are downregulated early in HD. Synopsis: This study models the transcriptional network controlling mouse and human striatum, and predicts a central role of 13 transcription factors whose regulatory network patterns change as a result of CAG expansion in Huntington's disease. A genome‐scale model for the target genes of transcription factors (TFs) in mouse and human striatum is built by integrating TF binding sites with transcriptomic data. The model identified 48 differentially expressed TF‐target gene modules associated with gene expression changes in Htt CAG knock‐in mouse striatum, and replicated many of these associations in independent transcriptomic and proteomic datasets. 13 of 48 of these predicted TF‐target gene modules were also differentially expressed in striatal tissue from human disease. Experimental validation of the model prediction that SMAD3 regulates HD‐related gene expression changes was produced using chromatin immunoprecipitation and deep sequencing (ChIP‐seq) of mouse striatum. Abstract : This study models the transcriptional network controlling mouse and human striatum, and predicts a central role of 13 transcription factors whose regulatory network patterns change as a result of CAG expansion in Huntington's disease.